World watch list for domestic animal deversity - FAO (FAO, 1995)
This book covers twenty-eight avian and mammalian species of farm animals and more than 120 species of their wild relatives. Within the farm animal species, breeds at high risk are defined as critical or endangered based on the number of breeding females or breeding males